Shuur sahi / Noor Afiqah Abdul Fattah - Abdul Fattah, Noor Afiqah (Faculty of Art and Design, 2020)
Shuur Sahi is a branding product of the sunnah diet. The Sahuur Sahi words derived from an Arabic word which means feeling healthy.